Pelatihan Praktik Pembelajaran Guru RA melalui Penyusunan Alur Tujuan Pembelajaran (ATP) Berbasis Teknologi - Dewi, Mutiara Sari; Sulistyani, Ika Ratih; Shafa, Inestha Luna Ratu; Zuhriya, Ida (Jurnal SOLMA, 2025)
Background: The implementation of the Independent Curriculum in Raudhatul Atfhal (RA) Wagir-Pakisaji District still faces challenges, especially in the preparation of the Learning Objectives Flow (ATP) and technology integration. This research aims to assist teachers in compiling contextual ATP while improving technology utilization skills in early childhood learning. The method used is Community Based Research (CBR) with the support of Rapid Rural Appraisal (RRA), involving RA teachers as active partners. Data were collected through observations, interviews, FGDs, and questionnaires, then analyzed in a simple qualitative and quantitative descriptive. The results showed that 78% of teachers need assistance in the preparation of ATP, while 84% do not understand the integration of technology, especially in the arrangement of toys. Through two-stage training and mentoring, teachers experienced significant improvements: understanding of basic concepts of ATP reached the good category (mean 3.9–4.4) and simple technology use skills increased (mean 3.7–4.1). Real products in the form of contextual ATP documents and the design of the arrangement of play equipment were successfully produced by teachers. The conclusion of this study shows that CBR-based workshops are effective in increasing the capacity of RA teachers, although technological integration still requires continuous strengthening. This activity has the potential to be replicated in other PAUD units as a strategy to optimize the implementation of the Independent Curriculum.